A queer history of the United States for young people - Chevat, Richie (Beacon Press, 2019)
Examines the history of homosexuality in America ranging from indigenous tribes who embraced diverse sexual orientation and gender identities to historical figures such as transgender war hero Albert D.J. Cashier and civil rights leader Bayard Rustin who have made lasting contributions in the history and culture of the LGBTQ community. Includes a glossary and photographs.